The impact of emotional flexibility on decision-making ethics: A Case study of the center of Najaf Governorate - Obaid, Hayder; Aziz, Ihsan; Yasir, Mohanad (The Arab Journal of Administration, 2021)
The impact of decision ethics on staff and the future of organizations in general has received a great deal of attention in organizational science, since the institutionalization of ethical practices often encourages individuals to believe more strongly that employers engage in ethical work. These beliefs often lead to a variety of positive job responses, so it is interesting to look at the entire ethical decision-making process, without distinguishing between recognition of ethical dilemmas and moral behavior. In this sense, our study came in an attempt to identify the objective of the study was to identify the effect of emotional flexibility through three dimensions (adaptability, main readiness and social arts) as an explanatory variable in the decision-making ethics as a responsive variable. The sample of the sample was (195) employees out of (293), and 187 questionnaires were retrieved (66%). The research included two main hypotheses for testing the relationship of correlation and effect between search variables. The results were extracted using the SPSS. The most important findings of the research are that the awareness of the individuals in the study sample and their response to the changing circumstances made them observe ethical behavior when making decisions concerning the future of the organization being investigated